Perbandingan Hasil Belajar Siswa Menggunakan Chromebook Ditinjau Dari Perbedaan Gender Pada Kelas V Semester 1 Di SD Negeri 20 Pangkalpinang - Enno Dwiputri; Fandi Nugroho; Erika Fitri Wardani (JBES (Journal Basic Education Skills), 2025)
It's critical for student learning outcomes when using Chromebook media without changing anything else or altering existing data. The purpose of this study is to identify differences in student learning outcomes used by the Choromebook media based on the gender distinctions between women and men. In this research, a quantitative approach was used in conjunction with the Ex Post Facto study method. This study dispersed all students in grade V at SD Negeri 20 Pangkalpinang, which amounted to 35 students. The data collection technique in this study uses documentation techniques to obtain data on student learning outcomes in science subjects that have been carried out by classroom teachers. This study uses descriptive analysis and inferential analysis to examnine the information. The findings of this investigation, which used the Mann-Whitney U test, showed that there was no significant difference in the learning outcomes of grade V students of SD Negeri 20 Pangkalpinang when they used Chromebooks. The test the findings indicartes that there wa no noteworthy difference in the learning outcomes of students using Chromebooks between boys and girls, with a significance value of 0.169>0.05. After the learning process was completed, the teacher's learning test scores showed the students' learning outcomes.